1991
DOI: 10.1111/j.1600-051x.1991.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal characteristics in individuals with varying form of the upper central incisors

Abstract: It has been suggested that the variation in the morphology of the human periodontium may be related to the shape and form of the teeth. Furthermore, the severity of symptoms of periodontal disease have been proposed to differ among these various morphologic entities or "biotypes". The aim of the present study was (i) to identify individuals with markedly different crown forms and (ii) to determine probing pocket depth, probing attachment level and amount of gingival recession that had occurred at different tee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
267
4
29

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(316 citation statements)
references
References 7 publications
(8 reference statements)
16
267
4
29
Order By: Relevance
“…This finding is consistent with previous studies in which they found that thick gingival biotype was more prevalent among their sample populations [1] [13].…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous studies in which they found that thick gingival biotype was more prevalent among their sample populations [1] [13].…”
Section: Discussionsupporting
confidence: 94%
“…But there is a great risk that this osseous barrier may be resorbed by a craterization stemming from the vertical situation of the implant plateform or the smooth collar of the implant, which may be of the type with a 1.5 horizontal projection. In a fashion similar to what happens around natural teeth 21 with thin periodontium, there can also be resorption of slim buccal walls of less than a mm, because of lack of sufficient inherent vascularity and insufficient resistant strength against the mechanical constraints associated with an implant. This impact concentrates essentially on the crestal zone so practitioners must be sure at least 2 mm of bone is present between the implant and lines representing the walls surrounding adjacent teeth ( fig.…”
Section: -Three-dimensional Positioningmentioning
confidence: 95%
“…Авторы также отметили, что рельеф поверхности десны тесно связан с контуром подлежащей кости. В последующем результаты исследований подтвердили, что фронтальные зубы с уз-кой формой коронки больше подвержены рецессии десны [82]. Установлена взаимосвязь между БД и толщиной ВКП [58,67].…”
Section: стоматология 2 2015unclassified